FRI0152 Active therapeutic immunization with TNF-kinoid in rheumatoid arthritis patients with secondary resistance to tnfα antagonists is safe and immunogenic. (23rd January 2014) - Durez, P.; Miranda, P.; Toncheva, A.; Berman, A.; Rillo, O.L.; Boutsen, Y.; Kehler, T.; Mociran, E.; Soto Saez, L.; Fautrel, B.; Mariette, X.; Sokalov, P.; et al.
Abstract : Background: Blocking TNF alpha (TNFα) with monoclonal antibodies (mAbs) has been successful in the treatment of rheumatoid arthritis. However primary and secondary resistances are frequent and impose treatment changes. Active immunization with a TNF-Kinoid that safely induces self polyclonal anti-TNFα antibodies (Abs) could be an alternative to anti-TNFα mAbs Objectives: We evaluated the immunogenicity and safety of TNF-K in patients with rheumatoid arthritis and secondary resistance to TNF blockers. Methods: TNFα-Kinoid (TNF-K, Neovacs SA, Paris, France) is an immunotherapeutic composed of recombinant human TNFα conjugated to KLH, inactivated and adjuvanted with ISA-51 emulsion. 40 patients with active rheumatoid arthritis (DAS28≥3.2) with history of positive clinical response to TNF-blockers followed by secondary failure (35% IFX, 30% ADA, 42.5% ETA) were enrolled in a double-blind, placebo-controlled, phase 2 study to evaluate three different intramuscular doses of TNF-K (90, 180, 360 mcg) and two immunization schedules (D0 and 28 or D0, 7 and 28). Immune responses were evaluated through titration of anti-TNFα and anti-KLH Abs. Clinical response was evaluated by the ACR and EULAR core set response. Results: No related serious adverse event has been reported. Few minor transient local and systemic reactions have been recorded following immunization. Anti-TNFα Abs were induced in 50%, 75% and 91% of patients at 90 mcg, 180 mcg and 360 mcg, respectively. 100% of patients with three injections of 180 or 360 mcg had immunogenic response against 67% in two injections groups. Among the 21 patients who developed anti-TNF Abs, 48% present a moderate to good response according to EULAR score as opposed to only 31% of the 16 patients without Abs. A mean decrease of -14% of the C reactive protein level is measured in patients with Abs while in patients without Abs, the mean CRP level increased by 5%The mean decrease of the DAS28 score is -0.8 points in patients with Abs while it is only -0.5 in patients without Abs. Conclusions: Active immunization with TNFα kinoid to induce a polyclonal, self-anti-TNFα antibody response is safe and immunogenic. A clinical and biological response were observed in some patients included in this preliminary phase 2 study and further studies are needed to confirm this new approach in RA. Disclosure of Interest: P. Durez: None Declared, P. Miranda: None Declared, A. Toncheva: None Declared, A. Berman: None Declared, O. L. Rillo: None Declared, Y. Boutsen: None Declared, T. Kehler: None Declared, E. Mociran: None Declared, L. Soto Saez: None Declared, B. Fautrel: None Declared, X. Mariette: None Declared, P. Sokalov: None Declared, E. Lucero: None Declared, T. Vlak: None Declared, S. Grazio: None Declared, K. Mastrovic: None Declared, R. Chirieac: None Declared, G. Grouard-Vogel Employee of: Neovacs, O. Dhellin Employee of: Neovacs, S. Ouary Employee of: Neovacs, B. Fanget Employee of: Neovacs, P. Vandepapelière Employee of: Neovacs, M.-C. Boissier Consultant for: Neovacs